2014
DOI: 10.2147/ppa.s64593
|View full text |Cite
|
Sign up to set email alerts
|

What puts heart failure patients at risk for poor medication adherence?

Abstract: BackgroundMedication nonadherence is a major cause of hospitalization in patients with heart failure (HF), which contributes enormously to health care costs. We previously found, using the World Health Organization adherence dimensions, that condition and patient level factors predicted nonadherence in HF. In this study, we assessed a wider variety of condition and patient factors and interactions to improve our ability to identify those at risk for hospitalization.Materials and methodsMedication adherence was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 57 publications
3
16
0
Order By: Relevance
“…However, individuals with good adherence had more hours sleep per night (average of 7 hours) compared to those from the poor adherence group (6 hours). Although the focus of this variable was on the quantity of sleep rather than quality, medication adherence can decrease with a reduction in sleep quality [43]. Perhaps inadequate and poor quality sleep can influence cognitive function [43], and the ability to pay attention and make good decisions [44].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, individuals with good adherence had more hours sleep per night (average of 7 hours) compared to those from the poor adherence group (6 hours). Although the focus of this variable was on the quantity of sleep rather than quality, medication adherence can decrease with a reduction in sleep quality [43]. Perhaps inadequate and poor quality sleep can influence cognitive function [43], and the ability to pay attention and make good decisions [44].…”
Section: Discussionmentioning
confidence: 99%
“…Although the focus of this variable was on the quantity of sleep rather than quality, medication adherence can decrease with a reduction in sleep quality [43]. Perhaps inadequate and poor quality sleep can influence cognitive function [43], and the ability to pay attention and make good decisions [44]. Impaired cognitive function may increase forgetfulness and unintentional medication non-adherence.…”
Section: Discussionmentioning
confidence: 99%
“…3) The adaptive multiple risk factors model was used to generate the associated risk index model for medication nonadherence, based on the count of that model’s risk factors. Interactions between risk factors were not considered in these subgroup analyses (as they were in analyses of the full data; Knafl & Riegel, 2014) because meaningful interaction results were unlikely given the modest subgroup sample sizes.…”
Section: Methodsmentioning
confidence: 99%
“…In the first two analyses, we used the World Health Organization dimensions of adherence (socioeconomic, condition, therapy, patient, and healthcare system) to focus our exploration of contributors to nonadherence (Riegel & Knafl, 2013; Riegel et al, 2012). In the third analysis, we tested a wide range of clinical and patient-related variables (demographic, social support, self-care, symptoms, and cognition) to avoid omitted variable bias (Knafl & Riegel, 2014). In a subsequent study we found that Blacks had poorer medication adherence than Whites (Dickson, Knafl, & Riegel, 2015).…”
Section: Research To Datementioning
confidence: 99%
“…Moreover, as more medications are used adherence and compliance to treatments often decrease and drug interactions and adverse effects become more common. 2 , 3 Prescription of complex regimens and the resultant nonadherence may potentially contribute to poor disease control, recurrent hospitalizations, and higher mortality. 4 , 5 Thus, polypharmacy is an issue of critical importance for geriatric patients and their prescribers.…”
Section: Introductionmentioning
confidence: 99%